La polilla Copitarsia decolora: revisión del complejo de especies con base en la morfología genital masculina y de los huevos (Lepidoptera: Noctuidae) - O. Angulo, Andrés (2010)
Copitarsia decolora is a widely distributed polyphagous species with a large number of nominal changes due to phenotypic plasticity. We reviewed 14 males from Mexico, Colombia, venezuela, Peru and Chile and the literature produced between 2003 and 2008. An analysis of the clasper com-plex of C. decolora male genitalia was performed by standard dissection. Scanning electron microscope (SEM) photographs of eggs structures were used as taxonomic characters. The genus Copitarsia comprises 23 species. C. corruda is considered a synonym of C. decolora.